Assessment of Long-Term Diabetes Medication Use and Its Effects on Osteoporosis Risk in Diabetic Patients - Muayad AL-dulaimi; Saad M. Saeed; Muayad AL-dulaimi (Jurnal MIPA dan Pembelajarannya, 2026)
Background; Diabetes mellitus is a metabolic and systematic disorder that requires individualized therapy. The disease leads to various consequences, resulting in the destruction of tissues and organs. The aforementioned outcomes also include bone mineral disorders, caused by medications as well as diet therapy and physical activity.  Objective; Assessment of osteoporosis risk in diabetic patients with  long-term diabetes medication use by detection some immunological and biochemical indicators. Material and methods; The current study was conducted in Baqubah city/ Diyala province for the period; 1/10/2024 to 1/3/2025. 50 blood samples were collected from diabetic patients with osteoporosis who went to Baqubah Teaching Hospital as well as to the outpatient clinics. Also, 30 blood samples were collected from healthy people and considered as a control group.  Serum levels of ACCP, CRP, CK-MP, Vitamin D3, calcium, and RF  in all samples were quantified by  AFIAS  Machine. Present data were programmed by SPSS v. 20.0 and Graph pad prism v.6 statistical software. Results; Present outcomes showed no significant differences (p>0.05) between males versus females and among age groups of patients. Also, current findings showed no significant differences between positivity of RF and study groups. Levels  of CRP and CK-MP were high in patients compared to controls , while levels of Vitamin D3 and  calcium were lowest in patients  than control . In contrast, present study showed no differences (p>0.05) between levels of ACCP and study groups. Based on gender, present research showed no differences between positivity RF and groups (male vs. female vs. control). The levels of CRP  and CK-MP scored highest mean level in males and lowest mean in females . On other hand, present findings showed the Vitamin D3  and calcium scored lowest level in males and highest mean in control . Finally, present study showed no differences (p>0.05) between levels of ACCP and groups (male vs. female vs. control). Conclusions;  The present study concluded the ACCP and RF indicator not play role in assessment osteoporosis in DM patients due to it isn’t levels affected by diseases, while CRP, calcium, CK-MB and vitamin D3 indicators have major role in assessment due to it is levels high affected by disease. Based on gender, present findings revealed there is variation in levels of CRP, calcium, CK-MB and vitamin D3 between males versus females due to hormonal and genetic disorders.